Digitalization of Facilities Management - The Slow Development of Space Management - Trevik, Simon; Nilsson, Tobias (My University, 2017)
The Facilities Management (FM) industry has to deal with a lot of information concerning facilities. This information needs to be handled, available and stored in a easy way for the facility manager to use. Previously this was done in an analog manner, but now digitalization of FM is an ongoing process. Building Information Modelling (BIM) could be a major part of this digitalization. New methods to perform FM services through digital tools such as BIM, are on the rise in the construction industry. These tools are however seldom used, even if the development of BIM in the field of FM is growing. One aspect of FM that may be improved with digital tools is Space Management (SM), which has the potential of reducing costs of both space and personnel. The aim of this thesis is to investigate how digitalization, especially BIM, can be used to support SM. This is done through mapping how facility managers utilize BIM for the purpose of SM today and to analyze how it can be improved. Through an abductive research approach a literature study and a qualitative empirical investigation were performed. The literature study served to compile knowledge for the thesis regarding FM, SM, BIM and associated methods and tools semi-structured interviews with facility managers as well as BIM- and FM-consultants were performed, to gather empirical information regarding how large property owners in the Gothenburg region perform SM. The literature study demonstrated the importance and benefits of efficient SM. Highlighted benefits include, decreased facility costs, improve business performance, keeping track of information that enables better decision-making concerning future business planning. Several reviewed authors mean that BIM has the potential to improve SM by, storage of information concerning spaces in one place, provide up to date information and graphics, up to date space utilization, and allows FM staff to make decisions that are well informed both visually and technically. BIM implementation is however costly for adopters since it involves new working methods, new software and knowledge about it. The study showed that higher profits were the most important issue among the property owners and one way to achieve this is to make sure that facilities are being fully utilized and spaces don’t stand empty or are forgotten. The facility manager’s own knowledge of the facilities is important, not many digital tools are used more than technical drawings, in the form of PDF-files. Some of the interviewed companies do however work with BIM models for their newly constructed facilities, but not for existing ones. There are differing views concerning BIM among facility managers, some do not find it beneficial enough to implement, while others see potential benefits, and wish for digital development in this direction. Even though some of the interviewed facility managers does not want to implement BIM, small steps towards digitalization have been seen among all property owners. In conclusion, the commercial property owners in Gothenburg do not perform SM with BIM tools. The facility manager’s knowledge and technical drawings is the information material that is used. Some of the interviewed managers do however want to use BIM more, while others do not. Digitalization is something many of them believe will increase. Even though the expression BIM may be used less because of prejudice among professionals, digitalization will most likely develop the work of SM and enable new working methods. Professionals interviewed for this thesis were more positive and optimistic towards digitalization than BIM.
Keywords: Samhällsbyggnadsteknik; Civil Engineering